Система підпорядкованого керування з селективною корекцією - Лозинський, Орест Юліанович; Панченко, Борис Якович; Карплюк, Леонід Федорович (НТУ "ХПІ", 2010)
The control system of electric drives has been analyzed. Method of tuning speed feedback adjusting was developed. The result can be used for the designing new systems of electric drives.
Control system with selective corection
Keywords: електропривід; швидкість; з'єднання контурів регулювання; ланка вибору режиму; режим пуско-гальмівний